Social and health-related policy priorities of adults with intellectual disability in South Africa - Zihlazi, Siphesihle (Department of Psychiatry and Mental Health, 2024)
Background: People with intellectual disability are rarely consulted on what should be prioritised in public policy to improve their quality of life. It is also well documented in the literature that people with intellectual disability experience barriers when accessing social and health services. The aim of the study is to gain an understanding of policy priorities from the perspective of people with intellectual disabilities. Method: The study is qualitative in nature, with data collected through a scoping review from 1994 to 2021 on policy priorities for people with intellectual disability, and semi-structured interviews on the views of South African adults with intellectual disability on their policy priorities. The study participants comprised a sample of six participants with intellectual disability, aged 18 years and older, who were recruited through a non-profit organisation that offers a range of services for people with psychosocial and/or intellectual disability and their families; ranging from counselling and support, special education and care centres for children and adults, as well as training and employment opportunities for those who are able to work. Results: Policy priorities identified in this study include the need for support in education and skills training, adequate healthcare access, work opportunities, inclusive housing, and supportive relationships. Conclusion: It is evident from the findings of this study that people with intellectual disability are still largely excluded from policy participation. Public policy makers and implementers should consider reasonable accommodations to enhance involvement of people with intellectual disability in discussions and decisions about policy and practice which impact on their lives. Research documenting the voices of people with intellectual disability can also assist to inform policy development and needs to include adaptations to data collection methods to optimise participants opportunities to share their views on what they need. Study implications: This study highlights the importance of reasonable accommodations for people with intellectual disability to inform policy developments, and the need to eliminate barriers encountered by people with intellectual disability when accessing social, health and other public services. Keywords: Intellectual disability, self-advocacy, lived-experiences, health policy, social policy